1990
DOI: 10.1001/jama.264.16.2109
|View full text |Cite
|
Sign up to set email alerts
|

Does age affect outcomes of out-of-hospital cardiopulmonary resuscitation?

Abstract: We examined the relation between age and outcomes in patients treated for out-of-hospital cardiac arrest in Seattle, Wash. Considering all out-of-hospital cardiac arrests treated by paramedics over a recent 5-year period, 386 (27%) of 1405 consecutive patients aged 70 years or older were resuscitated and admitted to a hospital vs 474 (29%) of 1624 younger patients; 140 elderly patients (10%) were discharged alive vs 223 younger patients (14%). Of the 140 elderly patients, 112 went home and 28 went to a nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
2
16
1
1
Order By: Relevance
“…Longstreth et al documented a 10% survival to discharge for all OHCA patients older than 70 and a 24% survival rate for patients with the initial arrest rhythm of VF in this age group. 31 Bonnin et al documented a 7% survival to discharge rate for the same age group, with a 14% survival rate for VF patients. 5 Van Hoeyweghen et al identified no significant difference in survival to discharge in a comparison of different age cohorts, but their definition of long-term survival was consciousness at 14 days after arrest.…”
Section: Discussionmentioning
confidence: 96%
“…Longstreth et al documented a 10% survival to discharge for all OHCA patients older than 70 and a 24% survival rate for patients with the initial arrest rhythm of VF in this age group. 31 Bonnin et al documented a 7% survival to discharge rate for the same age group, with a 14% survival rate for VF patients. 5 Van Hoeyweghen et al identified no significant difference in survival to discharge in a comparison of different age cohorts, but their definition of long-term survival was consciousness at 14 days after arrest.…”
Section: Discussionmentioning
confidence: 96%
“…This could have something to do with the fact that the proportion of first-grade first responders who could treat patients with professional CPR increased from 2.2% in 2006 to 4.7% in 2014, which led to more cases where AEDs were applied 24) . In addition, there could be many variables at play such as whether bystanders had witnessed cardiac arrest before, whether they had necessarily discovered a cardiac arrest patient, the underlying disease of a patient and bystanders' quality of performance of chest compressions [11][12][13][14][15] . AHA guidelines suggest swift activation of the emergency response system when there is no breath or reaction from a patient after bystander's discovery and assessment of the patient's consciousness 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these low survival rates, several studies suggested that performing CPR on elderly cardiac arrest patients should cease [6][7][8] . However, other studies found that there was no difference in survival rate after CPR between elderly and nonelderly cardiac arrest patients [9][10][11][12][13][14] . In order to raise the survival rate of cardiac arrest patients, it is necessary to ensure that each goal in the chain of survival is successfully met, including swiftly identifying a cardiac arrest, activating the emergency response system, performing early CPR that emphasizes chest compressions, and applying rapid defibrillation [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies involve a small number of patients, 6,[20][21][22][23][24][25][26][27][28] with a few exceptions, [29][30][31] and outcomes are mainly assessed by clinical judgment [21][22][23]26,27,30,31 and rarely by quantitative measurements. 9,10 When no important methodological differences exist, 9,10 our data suggest that across different studies, survivors after CPR have about the same quality of life, regardless of the conditions un- der which CPR took place.…”
Section: Commentmentioning
confidence: 99%